Job flexibility in Latin America: A comparative analysis - Manuel Alejandro Ibarra Cisneros (Estudios Fronterizos, 2010)
Most of studies about labor flexibility show a partial image of the situation of Latin America labor markets. They are limited to confirm, the existence of high degrees of rigidity and the necessity to conduct labor reforms to the margin of specific national circumstances. The design of a synthetic labor rigidity indicator using methodology considered by the oecd, through a factor analysis for countries of IberoAmerica, allows obtaining certain advances in relation to this debate. The results establish the high importance of the rigidity in the procedures of collective dismissal, over normative aspects related to fixed term contracts. Finally, it is establish the little relation between flexibility levels and results in terms of economic development, putting into question the assertions that try to extrapolate strategies of flexibilization like isolated measurement to facilitate the economic progress of a country.